Filarete Der Architekt der Renaissance als Demiurg und Pädagoge - Schütze, Sebastian; Hub, Berthold (2020)
Antonio di Pietro Averlino, called Filarete, in his Libro architettonico, written between 1460 and 1464 in the form of a dialogue between the author and Duke Francesco Sforza and his son Galeazzo Maria Sforza, tells of the planning, founding and construction of the city named after its owner »Sforzinda« and a city by the sea connected to it. In addition to the practical aspects of architecture and theory in the narrower sense, the first monographical examination of the Codex is also devoted to passages and illustrations that have hitherto been neglected or not at all Filaretes' source writings that go beyond the usual art-historical reference points to show Libro as an outstanding, crystalline document of its time as a whole, which expands and corrects our picture of the Renaissance, shaped by the winners of history.